2011
DOI: 10.3389/fimmu.2011.00040
|View full text |Cite
|
Sign up to set email alerts
|

Immune Recognition of Gene Transfer Vectors: Focus on Adenovirus as a Paradigm

Abstract: Recombinant Adenovirus (Ad) based vectors have been utilized extensively as a gene transfer platform in multiple pre-clinical and clinical applications. These applications are numerous, and inclusive of both gene therapy and vaccine based approaches to human or animal diseases. The widespread utilization of these vectors in both animal models, as well as numerous human clinical trials (Ad-based vectors surpass all other gene transfer vectors relative to numbers of patients treated, as well as number of clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 167 publications
(243 reference statements)
1
19
0
Order By: Relevance
“…27,28 Our present and previously published data have demonstrated that expression of EAT-2 during initial antigen presentation enhanced the production of proinflammatory cytokines and chemokines, as well as upregulated the expression of co-stimulatory molecules on the surface of APCs. 34,58 In this study, we focused on the kinetics and amplitude of cytokine and chemokine production levels following rAd5-EAT2 administration in vivo . Significantly, EAT-2 overexpression enhances the soluble proinflammatory repertoire by enhancing the production of the Th1-type-skewing cytokines (IFNγ, IL-12 and IL-1α) while minimizing the induction of Th2-type-enhancing cytokines (IL-10) and chemokines (EOTAXIN and KC).…”
Section: Discussionmentioning
confidence: 99%
“…27,28 Our present and previously published data have demonstrated that expression of EAT-2 during initial antigen presentation enhanced the production of proinflammatory cytokines and chemokines, as well as upregulated the expression of co-stimulatory molecules on the surface of APCs. 34,58 In this study, we focused on the kinetics and amplitude of cytokine and chemokine production levels following rAd5-EAT2 administration in vivo . Significantly, EAT-2 overexpression enhances the soluble proinflammatory repertoire by enhancing the production of the Th1-type-skewing cytokines (IFNγ, IL-12 and IL-1α) while minimizing the induction of Th2-type-enhancing cytokines (IL-10) and chemokines (EOTAXIN and KC).…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 45% of the healthy adult population in the United States and India, 72% in China and 80% in South Africa, Gambia and Thailand have serological evidence of PEI to Ad5 in the context of measurable anti-Ad5 neutralizing antibody (NAB) titers in the circulation 1215 . This may manifest as high levels of pro-inflammatory cytokines at the time the vaccine is given, a humoral antibody response that neutralizes the adenovirus, or a cellular immune response that targets and destroys cells expressing adenoviral antigens 11, 16 .…”
Section: Introductionmentioning
confidence: 99%
“…Adenovirus vectors transduce large fragments of DNA into a wide range of cells in order to synthesize proteins in vivo, and gene expression can be modulated and even localized to specific cell types. Unlike that for other types of viral delivery systems, the DNA delivered by adenovirus vectors does not integrate into the genome and thus the danger of insertional mutagenesis is circumvented (22). Adenovirus vectors have been shown to induce innate immunity, which is partially due to induction of the STING DNA recognition pathway (23).…”
mentioning
confidence: 99%